Endo - Perio Lesion -A Case Report - Mody, DR; Bhavsar, NV (Bangladesh Journal of Dental Research & Education, 2014)
Bacterial infections play an important role in the vast majority of pulpal and periodontal lesions. Such infections usually account for more than 500% of the tooth mortality. Endo-perio lesions primarily occur by way of the intimate anatomic and vascular connection. Accurate diagnostic tests must be carried out to confirm pulp necrosis and careful diagnostic probing should be done to distinguish between endo-perio lesions. DOI: http://dx.doi.org/10.3329/bjdre.v4i2.20273 Bangladesh Journal of Dental Research and Education Vol.4(2) 2014: 94-97